Approach for Development of Commercial Deer Farming Tourism Resource into Learning Resource: A Case Study of Pakdee Farm, Wang Thong District, Phitsanulok Province - Sanprasit, Ratchadaporn; Rangkhing, Rutchaneekorn (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2022)
This qualitative research aims to 1) study tourists’ behavior and satisfaction towards commercial deer farming, and 2) find an approach for development of commercial deer farming tourism resource into learning resource. Participants for the study was a specifically-selected group of 97 tourists who travelled to Pakdee farm at Wang Thong district, Phitsanulok province, 1 commercial deer farm entrepreneur, 10 villagers, and 4 community leaders from Ban Sam Takhian, Wang Nok Aen sub-district, Wang Thong district, Phitsanulok province. Tools used in this study were questionnaire and focus group discussion. Statistics used to analyze data are percentage, means, and standard deviation, together with content analysis according to specified items. Results of the study show that: 1) Tourists’ overall satisfaction towards commercial deer farm “Pakdee farm” at Wang Nok Aen sub-district, Wang Thong district, Phitsanulok province, is in high level (4.07), with the highest satisfaction in service provision aspect (4.14). 2) Results from focus group discussion suggest an approach for developing learning resource by conducting a study to survey and collect information about deer, background and tourism resource in community, then organize and present the collected data in suitable formats through various medias. Moreover, there should be activity space or place to enhance learning of tourists, as well as generation of activities and touring routes that connect with other tourism resources in the community. These findings provide useful approach for the development of tourism resource into community learning resource, in order to create various learning opportunities through touring experience and local way of life that will lead to life-long leaning.